Routing Protocols for GeoNet: A Survey - Taysi, Z. Cihan; Yavuz, A. Gokhan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
The last decade has witnessed the rapid development of intelligent transportation systems (ITS), which aim to improve transportation activities in terms of safety and efficiency. Intervehicle communication (IVC) is an important component of the ITS architecture that enables vehicles to communicate with other vehicles and roadside infrastructure. The GeoNet Project will bring IVC one step further by enabling transparent Internet Protocol connectivity between vehicles and the infrastructure. Integrating the IVC with existing infrastructure over Internet Protocol version 6 (IPv6) will also enable the use of multimedia services. Although GeoNet concluded its activity, several topics in the final specification were left open ended, including the definition of the car-to-car transport layer, multiradio support, congestion control, IPv6 encoding of GeoDestination, mapping of IPv6 addresses to GeoNet addresses, and GeoRouting protocol. This paper provides a survey of the existing GeoRouting protocols and evaluates the compatibility of these protocols with the GeoNet architecture.
Keywords: Car2Car Communication Consortium (C2C-CC); GeoNet; GeoRouting; infotainment; intelligent transportation systems (ITS); intervehicle communication (IVC); receiver-based routing; sender-based routing; COMMUNICATION-SYSTEMS; PERFORMANCE; BROADCAST; NETWORKS; DELIVERY; VEHICLES; DESIGN; SAFETY; Engineering; Transportation